Enhancing Interest in Religious Learning Through Board Games as a Learning Medium at Al-Husain Quranic Education Center (TPA), Purwokerto, Banyumas - Fuad Tamami; Hidayat, Fahri (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2025)
The decline in interest in religious learning in children is a challenge faced by many non-formal educational institutions, including the Al-Husain Al-Quran Education Park (TPA) in Purwokerto Wetan. This study aims to increase children's interest in religious learning through the application of board games as an interactive and enjoyable learning medium. The method used was classroom action research (CAR) with two cycles, each consisting of planning, implementation, observation, and reflection. The subjects of the study were students at the Al-Husain TPA in Purwokerto Wetan. Data were collected through observation, interviews, and a learning interest questionnaire. The results showed a significant increase in interest in religious learning after the application of board games. Children became more enthusiastic, active, and motivated in participating in learning. The use of board games has proven effective in creating a fun learning atmosphere and encouraging optimal student involvement. Thus, board games can be an innovative alternative in increasing